Etniczny wymiar depopulacji w Rosji w ujęciu regionalnym - Wiśniewski, Rafał (Przegląd Wschodnioeuropejski, 2018)
The paper addresses the issue of depopulation in Russia, especially the ethnic aspect of this process considering the regional approach. Two essential aspects of depopulation were discussed i.e., the quantitative aspect resulting from the rate of natural increase or decrease and migration, as well as the qualitative aspect exerting impact on changes in the number of ethnic groups, namely the shift in ethnic self-identification. The analysis was conducted for the period of 1989–2010 (the last census in the USSR and the last census conducted in the Russian Federation). Population change in Russia has acquired a specific meaning in regional terms, leading to significant quantitative and structural transformation. On the one hand, there is a depopulation of native Russian regions and ethnic structured regions dominated by the Russians (or more broadly by the Slavs), and on the other, demographic expansion of non- Slavic ethnic groups, especially of North Caucasus. Changing the mutual relations between ethnic groups may cause tension or escalation of ethnic conflicts.